Institutional Leadership that Disrupts: A Case of the National Football League - Calvin Nite; Briton Hagan (Journal of Applied Sports Management, 2018)
This research draws upon the concepts of institutional leadership to understand how institutional leaders may work to destabilize the contexts they are trying to maintain. We examined the discourse surrounding the recent controversies with the National Football League (NFL). Our findings suggest that the actions of NFL executives, including problematic decision-making and inconsistent practices, likely led to dissension among executives and an alienated workforce. We theorize that this could be destabilizing and lead to institutional disruption. The implications of this for theory and practice are discussed. Keywords: Institutional leadership, NFL, institutional disruption Subscribe to JASM
Keywords: Institutional leadership; NFL; Institutional disruption